Eye diseases: the neglected health condition among urban slum population of Dhaka, Bangladesh - Sutradhar, Ipsita; Sarker, Malabika (BMC ophthalmology, 2019)
Globally, eye diseases are considered as one of the major contributors of nonfatal disabling conditions. In Bangladesh, 1.5% of adults are blind and 21.6% have low vision. Therefore, this paper aimed to identify the community-based prevalence and associated risk factors of eye diseases among slum dwellers of Dhaka city.
Gesehen am 21.02.2019